Janice VanCleave's 202 oozing, bubbling, dripping, and bouncing experiments. - VanCleave, Janice Pratt (New York : J. Wiley, 1996)
Provides instructions for over two hundred experiments that ooze, bubble, drip, and bounce for children ages eight through twelve including projects for showing how craters form on the moon and using toothpaste to simulate a shield volcano.
Cover title: Janice VanCleave's 202 oozing, bubbling, dripping, & bouncing experiments.
Includes index.
School Library Journal.
Wilson's Children.
5.8.
5.8
Keywords: Science -- Experiments -- Juvenile literature; Scientific recreations -- Juvenile literature; Experiments; Science -- Experiments; Science -- Experiments; Scientific recreations